Komposisi Rotifera di Muara Sungai Kakap Kecamatan Sungai Kakap Kabupaten Kubu Raya - Ari Hepi Yanti, Agus Rianto, Tri Rima Setyawati (Universitas Tanjungpura, 2017)
Kakap River Estuary is a body of water in a direct contact with the sea and has a water salinity changes that affect the composition of Rotifera, is an estuarine ecosystem. The purpose of this study was to determine the species of Rotifera in the Kakap River Estuary. This study was conducted in May to August 2015. The sampling location was divided into seven stations, each station was divided into three sampling points, and each point of sampling was repeated three times. The research found 73 species of Rotifera belong to 14 genera (Anuraeopsis, Brachionus, Keratella, Beauchampiella, Euchlanis, Cephalodella, Colurella, Lepadella,Habrotrocha, Lecane, Philodina, Polyarthra, Trichocerca, and Testudinella). Lecane was the most common genera species found of all stations with a number of 33 species.